Propriedade intelectual, serviços e investmentos: Panorama de regulaç\~ao em acordos regionais de comércio celebrados por Uni\~ao Europeia, Estados Unidos, China e Índia - Jo\~ao Henrique Ribeiro Roriz; Lucas da Silva Tasquetto (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– This paper regards the regulation of intellectual property, services and investments in some preferential trade agreements. We analyze the systematization of intellectual property, services and investment rules contained in treaties signed by the United States, European Union, India and China in comparison with how the world trade system regulates them. Then, we present evaluations and trends to be considered by the Brazilian foreign policy. This work is the result of a research on Regulation of global trade, particularly on Regional and bilateral trade agreements, of the Institute for Applied Economic Research.
Keywords: K33; 330; preferential trade agreements; intellectual property; services; investments; United States; European Union; China; India